Transcatheter arterial embolization using imipenem/cilastatin sodium and microspheres for traumatic pseudoaneurysm: A case report. (December 2022) - Hirano, Takaki; Iwasaki, Yudai; Ishida, Tokiya; Tameta, Tadanobu; Kobayashi, Hiroko; Shinohara, Kazuaki
Abstract: For transcatheter arterial embolization (TAE) of pseudoaneurysms, when the culprit artery is too small or tortuous to be selected with a microcatheter, n-butyl-2-cyanoacrylate (NBCA) may be used as embolic material. Nevertheless, NBCA can cause inadvertent embolization and ischemic complications because liquid adhesives cannot be controlled precisely. In such cases, imipenem/cilastatin sodium (IPM/CS) could be used as an alternative to NBCA for TAE. However, TAE using IPM/CS for traumatic pseudoaneurysms has not been reported previously. Therefore, the possibility of using IPM/CS to embolize refractory traumatic pseudoaneurysms with small culprit arteries remains unknown. A previously healthy 51-year-old man sustained multiple traumatic injuries, including an open pelvic fracture. An emergency TAE for the pelvic fracture, massive blood transfusion, and emergency colostomy and cystostomy were performed on admission day, following which the patient was hemodynamically stable. However, he had repeated episodes of hematochezia due to pelvic pseudoaneurysm on days 18, 53, 60, and 70 after admission despite several TAE attempts using gelatin sponge, coils, and NBCA. During recurrence on day 70, we performed TAE using IPM/CS and microspheres, following which the pseudoaneurysm resolved without rebleeding or obvious ischemic complications. IPM/CS and microspheres could embolize, without rebleeding, the refractory pseudoaneurysm in small and tortuous culprit arteries that could not be embolized with NBCA. For embolization of traumatic pseudoaneurysms with severe tissue damage and small culprit arteries, NBCA might not be able to reach the bleeding point. In such cases, TAE using IPM/CS and microspheres could be a safe and effective procedure. Highlights: TAE of pseudoaneurysms is tricky when the culprit artery is too small or tortuous. NBCA, a liquid adhesive, can be used for TAE but cannot be controlled precisely. Imipenem/cilastatin sodium (IPM/CS) is an alternative to NBCA for TAE. Together, IPM/CS and microspheres can embolize a case of refractory pseudoaneurysm. There were no rebleeding or obvious ischemic complications in our case.